Penerapan Akad Murabahah di PT. BANK SYARIAH KCP MEDAN Padang Bulan - Putri Andini Al Khoiri (STIKes Ibnu Sina Ajibarang, 2024)
Sharia banks are currently on the rise and have become a reference for the public. One of them is 4.444 loans with a profit sharing system. Therefore, various sharia banking products, including the application of Murabahah contracts to PT financing products, must be understood by the wider community. Sharia People's Financial BANK SHARIA INDONESIA KCP MEDAN PADANG BULAN. This article explains the introduction of Murabahah contracts in PT loan products. People's Sharia Financial BSI KCP MEDAN PADANG BULAN This article uses qualitative research, collecting data through online interviews with PT manager BANK SHARIA INDONESIA KCP MEDAN PADANG BULAN. The result of this research is the application of a financing contract, namely the Murabaha contract, namely a contract for buying and selling goods at the original price with additional agreed profits. Technically, Sharia Banking Murabahah is defined as an agreement agreed between a sharia bank and a customer where the bank provides financing for the purchase of raw materials and other working capital needed by the custome.